Negosiasi Wacana Femininitas Melalui Film-Film Animasi Putri Disney - Arby, Sella Putri; Rahayu, Lina Meilinawati; Mulyadi, R M (Paradigma: Jurnal Kajian Budaya, 2022)
Negotiation Discourse of Femininity Through Disney Princesses’ Movies. Femininity tends to be explained as a condition ‘to be a woman’, making it an ideology that gives limitations to women. Mills uses discourse theory to explain femininity, stating femininity is a process that is constructed and negotiated in every interaction. Disney Princesses show changes through times and each animation film, showing a negotiation of what defines femininity. The data collection was carried out by qualitative method narrative study, with Performativity of Gender by Judith Butler and Negotiation Discourse of Femininity theory by Sara Mills. Thirteen Disney Princesses were used as researched objects to show the slow changing of femininity. The results of this study show a change in Disney Princesses, through long negotiations based on the wave of feminism that occurred with the Disney Princess characters featured. Indications have shown through the Disney Princess characters who initially showed only stereotypes of feminine elements—such as being passive, gentle, not leaving their safe zone, becoming a Disney Princess who also showed stereotypical masculinity elements— such as being physically active, not easily afraid to discover new things, and showing bravery. This slow shift does not change the identity of Disney Princesses as a princess and as a woman.